Fungsi Hukum Administrasi Negara Terhadap Pengawasan Kebijakan Publik Dalam Penyelenggaraan Anggaran Dana Pemenuhan Pendidikan - Ar Rasyid, M. Afif; Daulay, Nisrina Ramadhani; Octaviyani, Rahma (Widya Yuridika, 2025)
Education is an important element for the progress of the nation and state. Decent education reflects the country's success in meeting society's needs. The public's need for education arises from the existence of social phenomena which have implications, public policy becomes a rule that is supervised by law in its implementation. In practice, policy implementation is still difficult to monitor, considering that many policies do not function according to their objectives. Free education is a public policy product that should be implemented so that all people can receive free education from elementary, middle and high school. Aiming at increasing the nation's intelligence in developing human resources, people no longer need to pay money to carry out education because education costs are the responsibility of the state. The method used is normative juridical using legal materials in the form of literature studies or secondary book materials and related cases. This research discusses several schools that implement free schools but still charge fees such as school construction fees, uniform fees, and other fees. By examining how administrative law monitors the implementation of public policies that have been implemented so that they are implemented according to their objectives. Analyzing what factors free education is not fully implemented. So there needs to be coordination and structured collaboration in implementing the free education policy in schools.